Uncertain Intellectual Property Conditions and Knowledge Appropriation: Evidence from the Genomics Industry - HUANG, Kenneth Guang-Lih (Institutional Knowledge at Singapore Management University, 2012)
Innovating technology firms often endure a sustained period of uncertain intellectual property rights (IPR) protection before patents could be granted to their valuable knowledge assets. This problem is exacerbated as firms increasingly develop their innovations or operate in countries with weak IPR institutional environments. But how does IPR uncertainty affect firms’ propensity toward knowledge appropriation– capturing of economic value from their knowledge assets– and toward providing access to these assets? We address this question using matching genomics patents and papers covering 362 firms. Under uncertain IPR conditions, firms disclose and accumulate more knowledge through open science (follow-on publishing) but shift to knowledge appropriation through commercial science (follow-on patenting) after IPR uncertainty is narrowed. This effect is most salient when firms develop their knowledge assets or operate under strong IPR institutions. For highly science-based assets, firms continue tapping into open science for access and reciprocity in knowledge acquisition from scientific community.